EXPERT SYSTEM OF PREECLAMPSIA DIAGNOSIS USING CERTAINTY FACTOR METHOD - Tarigan, Kiki Dea Ananda; Simanjuntak, Magdalena; Maulita, Yani (Yayasan Bina Internusa Mabarindo, 2024)
Preeclampsia is an increase in blood pressure and excess protein in the urine that occurs after more than 20 weeks of pregnancy. If not treated immediately, preeclampsia can cause complications that are dangerous for the mother and fetus. One factor that can increase the risk of preeclampsia is the age of pregnant women who are under 20 years or more than 40 years. This condition needs to be treated immediately to prevent complications or develop into preeclampsia that can threaten the lives of pregnant women and fetuses. The causes of preeclampsia are still not exactly known. However, this condition is thought to occur due to abnormalities in the development and function of the placenta, which is an organ that functions to deliver blood and nutrients to the fetus. The use of internet technology makes it easier for humans to access information without limited space and time and facilitates the design of expert systems to diagnose preeclampsia in mothers, and is expected to reduce or even eliminate existing problems, Therefore, an application is needed that can help to diagnose preeclampsia by using the certainty factor method which is easier and becomes an alternative in providing more knowledge about the results of preeclampsia diagnosis in pregnant women and can provide advice and consultation media about preeclampsia disease in patients and can reduce the cost of consulting an expert. Based on the calculation of CF, the highest value is the type of preeclampsia with a value of 0.9939 or 99.39%. From the results obtained, the system identifies that the patient has a type of preeclampsia.